IMPLEMENTATION OF ILLUSTRATED STORY MEDIA IN IMPROVING STUDENTS' READING COMPREHENSION - Winarni, Dian (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2025)
This study aims to describe the implementation of picture story media in improving reading comprehension skills of third-grade elementary school students. The research employed a qualitative approach with a descriptive method. Data were collected through observations, interviews, and documentation involving teachers and students during the Indonesian language learning process. The results show that picture story media effectively attract students’ attention, increase their interest in reading, and help them better understand the content of the texts. Moreover, active student engagement during learning activities contributes to the development of meaningful learning experiences